Levels of clinical complexity of adolescents eligible for palliative care assisted in a reference center in Uruguay (Archives of Pediatrics of Uruguay, 2025)
Introduction: the increase in life-limiting conditions in adolescents requires their characterization, so as to be able to identify their needs, prioritize their care, define the best-case scenario and follow-up the teams.Objective: to describe the characteristics and levels of clinical complexity of adolescents assisted by the Pediatric Palliative Care Unit of the Pereira Rossell Hospital Center between 2022 and 2023.Methodology: retrospective study reviewing medical records. All adolescents from 10 to 19 years of age in active care were included. We researched sociodemographic variables, life-limiting conditions and special needs grouped into 8 categories: care by specialists; chronic need for medication; special food to live; technological assistance; rehabilitation; special education; fragility and social complexity. In order to categorize the level of complexity, we used the modified care and classification model for Children and Adolescents with Special Health Care Needs.Results: 94 adolescents were included, 51% female, median age 13,4 years, 70,2% with chronic non-evolving encephalopathies; 97% attended continuous consultations with specialists; 90,4% used drugs chronically; 33% used special nutritional formulas; and 60% used medical technology; 65% underwent rehabilitation therapies and 79% attended educational centers; 89,4% required at least one hospital admission in the last year and 15% had social complexity. 75% were classified as having low clinical complexity and 26% as having medium clinical complexity.Conclusions: most adolescents were classified as having low clinical complexity. Understanding the level of complexity will allow improving the clinical management of care by optimizing available resources.
Keywords: Palliative Care; Adolescent